2012
DOI: 10.3928/1081597x-20121011-02
|View full text |Cite
|
Sign up to set email alerts
|

Results of Corneal Collagen Cross-linking in Pediatric Patients

Abstract: Corneal collagen CXL was found to be safe and effective in the first 12 months for keratoconus in children with similar initial efficacy as in adults in terms of improvement in visual and topographic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(74 citation statements)
references
References 16 publications
2
68
0
2
Order By: Relevance
“…A 3-year follow-up after epi-off CXL showed significant improvement in both visual acuity and keratometric values and a reduction in coma aberrations. Similarly, positive results were demonstrated in two smaller prospective pediatric trials [139,140]. …”
Section: Resultsmentioning
confidence: 89%
“…A 3-year follow-up after epi-off CXL showed significant improvement in both visual acuity and keratometric values and a reduction in coma aberrations. Similarly, positive results were demonstrated in two smaller prospective pediatric trials [139,140]. …”
Section: Resultsmentioning
confidence: 89%
“…5,17,152 Eyes with more advanced keratoconus show more flattening during the first year. 136 A longer-term study followed patients for three years, finding that, despite the initial improvement in parameters during the first year, some pediatric patients may continue to progress long term.…”
Section: Pediatric Keratoconusmentioning
confidence: 97%
“…All authors reported stabilization or flattening of corneal keratometry and stabilization or improvement of visual acuity after standard epi-off procedure. Long-term comparative analysis showed that functional results after CXL among pediatric and young patients (up to 26 years) were better than in patients over 27 years [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] .…”
Section: Standard Procedures and Clinical Resultsmentioning
confidence: 99%